2015
DOI: 10.1108/md-05-2014-0311
|View full text |Cite
|
Sign up to set email alerts
|

Home institutions, internationalization and firm performance

Abstract: Purpose – The purpose of this paper is to examine how home institutions moderate the influence of internationalization, and the effect this has on the performance of stock-listed Chinese firms. Design/methodology/approach – A sample of 118 stock-listed Chinese firms over the period 2006-2011 was considered, using the panel data method. Findings – The results show that foreign owne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 53 publications
2
21
0
2
Order By: Relevance
“…Studies of firm performance show main and interactive effects of institutions. Chen, Zhai, Wang, and Zhong () examine how home institutions moderate the relationship between internationalization and performance of 118 stock‐listed Chinese firms over the period 2006–2011. They find that foreign ownership and region‐specific marketization help firms reap the performance benefits of internationalization, while state ownership plays an insignificant role.…”
Section: Hypothesesmentioning
confidence: 99%
“…Studies of firm performance show main and interactive effects of institutions. Chen, Zhai, Wang, and Zhong () examine how home institutions moderate the relationship between internationalization and performance of 118 stock‐listed Chinese firms over the period 2006–2011. They find that foreign ownership and region‐specific marketization help firms reap the performance benefits of internationalization, while state ownership plays an insignificant role.…”
Section: Hypothesesmentioning
confidence: 99%
“…In summary, Filatotchev and Piesse [10] studied the experience of MNCs of 711 SMEs entrepreneurs and found that the market share sales growth pretax gross profit is negatively correlated; but the interaction effect between the two is positively correlated. Recently, Chen et al [20] considered a sample of 118 listed companies from 2006 to 2011 and found that private and specific regional marketization helps companies obtain international performance gains, while public operation plays a negligible role. e role of Zhou [21] studied 535 manufacturing companies of A-share listed companies from 2001 to 2014. e overall sample's international performance relationship is W-shaped, but changes with the size of the company.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the research on the impact of internationalization on company performance has different results, irrelevant [23][24][25], linear [19,20,26,27], U shape [6,18,21,28,29], S type [17], and higher power W type [21], and different external factors will have different effects.…”
Section: Introductionmentioning
confidence: 99%
“…First, we contribute to institutional theory and the IB literature. Prior studies have focussed on the heterogeneous internationalization behavior of firms responding to institutional pressures (Chen et al, 2015a;Cui and Jiang, 2012;Pan et al, 2014;Peng et al, 2008). Our study extends the literature by proposing that the antecedents of internationalization vary with the different levels of state capitalism.…”
Section: Introductionmentioning
confidence: 51%